The role of human rights lawyers in rights based approach to reduction of poverty in Sub-Saharan Africa - Mbazira, Christopher (University of Pretoria, 2008)
Mini Dissertation (LLM (Human Rights and Democratisation in Africa))--University of Pretoria, 2005.